Simulation study of summer microclimate in street space of historic conservation areas in China: A case study in Changsha - Liu, Junyou; Tang, Haifang; Zheng, Bohong (Frontiers in Environmental Science, 2023)
The renewal approach of historic conservation areas based on microclimate enhancement is critical for increasing residents' living comfort in these places. The ENVI-met simulation program is utilized in this paper to create a 3D model using Taiping Street Area as an example. The effects of street interface density, open space, D/H (the ratio between the width of a street and the height of its surrounding buildings), and other factors on the microclimate environment are fully considered through local "micro transformation" . This study found that the effect of wind passages on improving the thermal comfort of historical blocks is not significant, while that of building shadows is more significant. A local renewal strategy for the street space form is provided by changing street interface density suitably (There are significant differences in thermal comfort optimization strategies between north-south and east-west streets.), setting the open space in the base properly, and increasing the building height. The research findings can be used to optimize street space in terms of microclimate improvement and as a reference for the renewal of historic conservation zones, resulting in a more comfortable living environment.